2011
DOI: 10.1063/1.3562255
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and structural characterization of LiF tunnel barriers in organic spin-valve structures

Abstract: The electronic, magnetic, and structural properties of Ni80Fe20 and Co electrodes at LiF and aluminum tris(8-hydroxyquinoline), or Alq3, interfaces were investigated with photoemission spectroscopy and polarized neutron reflectivity measurements. When LiF was deposited onto Ni80Fe20 films and Co was deposited onto thin LiF layers, the work function of both metals decreased. Polarized neutron reflectivity measurements were used to probe the buried interfaces of multilayers resembling a spin-valve structure. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[22b] At present, the methods to optimize the fabrication of spin valve devices mainly include inserting an isolation layer, reducing the energy of deposited metal particles, reducing the junction area, and transferring electrodes. LiF [77,87] and AlO x [66,[81][82] are often used as protecting layers to prevent metal atoms from penetrating into organic layers. However, LiF has certain reactivity, which will lead to the fluorination of metal electrodes.…”
Section: Preparation Of Reliable Organic Spin Valvesmentioning
confidence: 99%
“…[22b] At present, the methods to optimize the fabrication of spin valve devices mainly include inserting an isolation layer, reducing the energy of deposited metal particles, reducing the junction area, and transferring electrodes. LiF [77,87] and AlO x [66,[81][82] are often used as protecting layers to prevent metal atoms from penetrating into organic layers. However, LiF has certain reactivity, which will lead to the fluorination of metal electrodes.…”
Section: Preparation Of Reliable Organic Spin Valvesmentioning
confidence: 99%
“…The interface between the top electrode and the organic semiconductor has also been studied, by investigating different interface layers between them. Schulz et al [18], Dhandapani et al [5] and Szulczewshi et al [19] all investigated using LiF as an interface layer between Alq 3 and the top electrode. Dhandapani showed that it improved the MR of FeCo/Alq 3 /NiFe spin-valves, while Schulz showed that the presence of LiF reversed the net extracted spin polarisation at the NiFe cathode, which resulted in the change in sign of the MR.…”
Section: Accepted Manuscriptmentioning
confidence: 99%